Etifoxine, a TSPO Ligand, Worsens Hepatitis C-Related Insulin Resistance but Relieves Lipid Accumulation. (11th March 2019) - Lin, Yu-Min; Sun, Hung-Yu; Chiu, Wen-Tai; Su, Hui-Chen; Chien, Yu-Chieh; Chang, Heng-Ai; Chong, Lee-Won; Chang, Hung-Chuen; Young, Kung-Chia; Bai, Chyi-Huey; Tsao, Chiung-Wen
Abstract : Etifoxine, an 18 kDa translocator protein (TSPO) agonist for the treatment of anxiety disorders in clinic, may be able to cause acute liver injury or cytolytic hepatitis. TSPO has been demonstrated to participate in inflammatory responses in infective diseases as well as to modulate glucose and lipid homeostasis. Hepatitis C virus (HCV) infection disrupts glucose and lipid homoeostasis, leading to insulin resistance (IR). Whether TSPO affects the HCV-induced IR remains unclear. Here, we found that the administration of etifoxine increased the TSPO protein expression and recovered the HCV-mediated lower mitochondrial membrane potential (MMP) without affecting HCV infection. Moreover, etifoxine reversed the HCV-induced lipid accumulation by modulating the expressions of sterol regulatory element-binding protein-1 and apolipoprotein J. On the other hand, in infected cells pretreated with etifoxine, the insulin-mediated insulin receptor substrate-1/Akt signals, forkhead box protein O1 translocation, and glucose uptake were blocked. Taken together, our results pointed out that etifoxine relieved the HCV-retarded MMP and reduced the lipid accumulation but deteriorated the HCV-induced IR by interfering with insulin signal molecules.